DETERMINATION OF MOISTURE CONTENT AND STORAGE POTENTIAL OF GUANANDI SEEDS - Silva, Rosemeire Carvalho; Grzybowski, Camila Ribeiro de Souza; Belniaki, Andreza Cerioni; Vieira, Elisa Serra Negra; Panobianco, Maristela (Floresta, 2019)
Guanandi is a native forest species with particularities that make it difficult to store of seeds, because of its recalcitrant behavior and since a specific and practical protocol to determine the moisture content of its seeds is not available yet. This work had the purpose to test procedures to determine the moisture content and to study different environmental conditions of the storage of the guanandi seeds. In order to determine the moisture content, the low-temperature oven method at 101 – 105°C was used, testing seed preparation methods (intact, cut in half and fragments smaller than 7.0 mm) and different drying periods. Four environments (wet chamber, dry chamber, cooler and laboratory environment) were tested for the storage of the seeds, with two packaging types, during four periods (0, 1, 2, 3 and 4 months). For the statistical analysis, a completely randomized design, with a factorial arrangement, was used for moisture content; a split-split plot design was used for storage. A regression analysis was performed to evaluate the physiological potential and moisture content during the storage, adjusting the significant equation by Tukey’s test. From the obtained results, it was observed that the low-temperature oven method 101 - 105°C / 17 h, using intact seeds, should be used to determine the moisture content of guanandi seeds. The best combination of environment and packaging to store seeds was the laboratory environment condition (average between 19.6 - 23.1 °C and RH 53-62%) in polyethylene packaging.